2017
DOI: 10.1371/journal.ppat.1006459
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania donovani resides in modified early endosomes by upregulating Rab5a expression via the downregulation of miR-494

Abstract: Several intracellular pathogens arrest the phagosome maturation in the host cells to avoid transport to lysosomes. In contrast, the Leishmania containing parasitophorous vacuole (PV) is shown to recruit lysosomal markers and thus Leishmania is postulated to be residing in the phagolysosomes in macrophages. Here, we report that Leishmania donovani specifically upregulates the expression of Rab5a by degrading c-Jun via their metalloprotease gp63 to downregulate the expression of miR-494 in THP-1 differentiated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 58 publications
6
43
0
1
Order By: Relevance
“…Moreover, L. donovani LPG promotes the accumulation of periphagosomal F-actin ( Holm et al, 2001 ) ( Winberg et al, 2009 ), avoiding in this manner the phagosome acidification and favoring the parasite intracellular survival ( Figure 2B ). The L. donovani metalloprotease GP63 (a surface and secreted glycoprotein of 63 kDa) downregulates miR-494, which induces Rab5a expression in the phagosome to prevent lysosome fusion ( Figure 2C ) ( Verma et al, 2017 ). Moreover, the cysteine peptidase B from L. mexicana regulates GP63 expression, thus indirectly influencing phagosome formation ( Casgrain et al, 2016 ).…”
Section: Macrophages As Key Hosts and Effectors Against Leimentioning
confidence: 99%
“…Moreover, L. donovani LPG promotes the accumulation of periphagosomal F-actin ( Holm et al, 2001 ) ( Winberg et al, 2009 ), avoiding in this manner the phagosome acidification and favoring the parasite intracellular survival ( Figure 2B ). The L. donovani metalloprotease GP63 (a surface and secreted glycoprotein of 63 kDa) downregulates miR-494, which induces Rab5a expression in the phagosome to prevent lysosome fusion ( Figure 2C ) ( Verma et al, 2017 ). Moreover, the cysteine peptidase B from L. mexicana regulates GP63 expression, thus indirectly influencing phagosome formation ( Casgrain et al, 2016 ).…”
Section: Macrophages As Key Hosts and Effectors Against Leimentioning
confidence: 99%
“…Rab5a localizes to early endosomes and regulates receptor-mediated endocytosis, actin cytoskeleton and T cell migration through Rho GTPase family protein Rac (Ong et al 2014 ). Leishmania donovani infection has been shown to upregulate Rab5a expression in human macrophages, thereby blocking lysosome fusion with early endosomes and facilitating parasite survival in human phagocytes (Verma et al, 2017 ). Our study showed downregulation of Rab5a expression in the △ MetQ treated group, and Rab5a downregulation in △ MetQ treated group might contribute to the attenuated survival of △ MetQ in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…and its eectors as a way to avoid neutralisation by the immune system or facilitate invasion (Verma et al, 2017). L. donovani specically controls the expression and function of the Rab5a isoform in this context (Verma et al, 2017).…”
Section: Details Of Mcmcmentioning
confidence: 99%
“…and its eectors as a way to avoid neutralisation by the immune system or facilitate invasion (Verma et al, 2017). L. donovani specically controls the expression and function of the Rab5a isoform in this context (Verma et al, 2017). Additionally, Rab5 was shown to participate in adenovirus endocytosis (Rauma et al, 1999), both Rab5a and Rab5b were found to play functional roles in web formation and viral genome replication during HCV (hepatitis C virus) infection (Stone et al, 2007), and Rab5a was identied as a crucial target of HBV (hepatitis B virus) during HBV-related hepatocellular carcinoma pathogenesis (Sheng et al, 2014).…”
Section: Details Of Mcmcmentioning
confidence: 99%